2019
DOI: 10.1111/obr.12855
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity in relation to readmission and all‐cause mortality following coronary artery bypass grafting: A systematic review and meta‐analysis

Abstract: Summary This study systemically reviewed evidence linking adiposity to readmission and all‐cause mortality in post‐coronary artery bypass grafting (CABG) patients. Keyword/reference search was performed in PubMed, Web of Science, CINAHL, and Cochrane Library for articles published before June, 2018. Eligibility criteria included study designs: experimental/observational studies; subjects: adult patients undergoing CABG; and outcomes: hospital/clinic readmissions, and short‐term (≤30 days) and mid‐to‐long‐term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Another meta-analysis focusing on CABG patients showed that the odds of post-CABG mid-to-long-term mortality were lower in overweight patients than in normal-weight patients, although that was not the case in obese patients. In fact, the latter had a similar risk for all-cause mortality to their normal-weight counterparts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis focusing on CABG patients showed that the odds of post-CABG mid-to-long-term mortality were lower in overweight patients than in normal-weight patients, although that was not the case in obese patients. In fact, the latter had a similar risk for all-cause mortality to their normal-weight counterparts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking history [ 12 ] is another factor that increases the risk of death from any cause in patients with coronary artery disease who undergo CABG. On the other hand, some studies have reported lower mortality and fewer adverse cardiovascular events and hospital readmissions after CABG in overweight patients [ 13 , 14 , 15 ]. Postoperative complications such as atrial fibrillation [ 16 ] and acute kidney injury [ 17 ] are associated with higher short-term and long-term mortality after CABG, as well as longer stays in the intensive care unit and hospital [ 2 ].…”
Section: Introductionmentioning
confidence: 99%